An Exploration of Fourth-Semester Students’ Perceptions on How Vocabulary Mastery Affects Their Speaking Ability at UNPARI - Nabilah Khairunnisa (CV Grasta Glory, 2025)
Vocabulary plays a central role in English as a Foreign Language (EFL) learning, particularly in speaking performance. This study explores the perceptions of fourth-semester English Education students at Universitas PGRI Silampari (UNPARI) regarding how vocabulary mastery affects their speaking ability. Using a qualitative descriptive method, data were collected through open-ended questionnaires and analyzed thematically. The findings revealed four major themes: speaking anxiety due to lexical limitations, compensatory strategies, vocabulary’s role in message clarity, and the need for more contextual vocabulary instruction. These insights offer implications for designing integrated vocabulary and speaking instruction in EFL contexts.